Interactive Video Learning Media Based on Canva with a Behaviorist Approach to Enhance Literacy in Elementary Students' Expository Text Learning - Nurlaeli, Nisa; Riskha Arfiyanti (Universitas Swadaya Gunung Jati, 2025)
This research seeks to evaluate the efficacy of employing Canvabased learning tools, specifically interactive videos, to enhance theexplanatory writing abilities of elementary school pupils through abehaviorism framework. The incorporation of digital technology ineducation is a crucial requirement for addressing the challenges of21st-century learning and specifically enhancing students' literacyabilities. This research employs a qualitative descriptivemethodology with a systematic literature review (SLR) strategy,incorporating the examination of diverse literary sources includingjournals, articles, books, and relevant research papers. The researchrevealed that using Canva-based interactive videos enhancesstudents' comprehension and writing abilities by deliveringeducational content in a more engaging, interactive, andcomprehensible manner. The behaviorism method centered onreinforcement and repetitive practice has proven to be effective inenhancing student motivation and involvement in the learningprocess. Nonetheless, its execution encounters multiple obstacles,such as insufficient technological infrastructure and a deficiency inteacher proficiency in creating digital educational resources.Addressing these challenges, the implementation of Canva-basedinteractive videos offers a creative way to enhance the quality ofexplanatory text education in elementary schools. The findings of thisresearch intend to aid in the creation of more efficient and creativeeducational tools in the digital age.